Ser niño: una nueva mirada de la infancia en el Perú - Alarcón, Walter (Serie "Infancia y sociedad", 1994)
"An excellent compilation of information on the conditions of underprivileged children in Peru who make up over 60 percent of the population under the age of 18. These children at risk are found working in the street, often homeless, and are sometimes caught in the civil war. Alarcon used several different sources of secondary data including national surveys, as well as original data gathered from in-depth interviews and a survey applied in metropolitan Lima"--Handbook of Latin American Studies, v. 57